Making Work Pay: U.S. American models for a German context? - Laura Chadwick; Jürgen Volkert (Institut für Angewandte Wirtschaftsforschung (IAW), 2003)
This paper examines efforts to make work pay, concentrating on U.S. American and German policies and experiments. We are specifically interested in fleshing out the relevance of U.S. American models for a German context as well as the special characteristics of the German situation which do not allow a mere copying of the models. There is no established negative income tax in Germany, but current experiments are being conducted, in order to assess how successful incentives could be in lowering the high levels of welfare caseloads and easing the transition from welfare to work. High unemployment rates and guaranteed social assistance (and unemployment insurance) have caused a German version of the poverty trap, where few incentives exist for people to find work. This paper examines the normative, political and economic situation of each country with specific experiments and studies of tax credits. The U.S. American early negative income tax (NIT) experiments in the 1970s, the present day Earned Income Tax Credit (EITC), and two recent experiments to make work pay are discussed. The historical, political and economic context of Germany is evaluated for a possible earned income tax credit, and fledgling tax credit experiments that are currently being conducted in Germany are discussed. A negative income tax is defined in this paper as a cash payment to individuals and families from respective governments that acts to subsidize personal income up to a predetermined level. There is a minimum benefit level, a marginal tax rate and a break-even point. The higher the benefit level and the break-even point, the more a negative income tax will cost the government (Zimmerman 1995). Before describing specific tax programs, we first outline the country's welfare state developments with respect to financial incentives for work. The following is a closer consideration of the U.S.-American and German public assistance and tax systems. The U.S. and Germany have very different welfare regimes and negative income taxes should inevitably fit into the respective welfare structures in different ways, fulfilling different goals.
Keywords: 330; Aktivierende Sozialhilfe; Niedriglohn; Lohnsubvention; Steuervergünstigung; Grundeinkommen; Öffentliche Sozialleistungen; Reform; USA; Deutschland